2018
DOI: 10.1016/j.yrtph.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the exposure to harmful and potentially harmful constituents in healthy Japanese smokers using a novel tobacco vapor product compared with conventional cigarettes and smoking abstinence

Abstract: The objectives of this clinical study were to demonstrate a reduction in exposure to selected harmful and potentially harmful constituents (HPHCs), and to assess product use behavior, in Japanese healthy adult smokers who switched to a novel tobacco vapor product (NTV). 60 smokers were randomly assigned for 5 days to either (a) a group who switched to an NTV (n = 20), (b) a group who continued to smoke their own brand of conventional cigarettes (CC, n = 20) or (c) a smoking abstinence group (SA, n = 20). Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Because the risk of smoking-related diseases is dose-dependent [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ], a significant reduction in toxicant emission can be expected to result in a significant reduction in toxicant exposure in human subjects who switch from cigarette smoking to a candidate MRTP in clinical studies. Ideally, this exposure reduction should approach the effect of complete smoking abstinence [ [37] , [38] , [39] , [40] , [41] , [42] ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the risk of smoking-related diseases is dose-dependent [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ], a significant reduction in toxicant emission can be expected to result in a significant reduction in toxicant exposure in human subjects who switch from cigarette smoking to a candidate MRTP in clinical studies. Ideally, this exposure reduction should approach the effect of complete smoking abstinence [ [37] , [38] , [39] , [40] , [41] , [42] ].…”
Section: Introductionmentioning
confidence: 99%
“…A short-term clinical study reported that smokers who switched to NTV showed a decrease in levels for biomarkers that indicate CS exposure (Yuki et al, 2018). The study provides the difference in the state of exposure, whereas in vitro studies using 3D cells provide the difference in functional change and organizational morphology.…”
Section: Biological Implications Of the Resultsmentioning
confidence: 99%
“… Exposure to carcinogenic toxicants A significant reduction in carcinogenic toxicant emission should then lead to a significant reduction in exposure to these substances in human subjects who switch from cigarette smoking to using a cMRTP in clinical studies. Ideally, these levels of exposure reduction should approach the levels of reduction observed in study subjects who abstained from smoking for the duration of the study [3639]. As a direct consequence of a reduction in exposure to carcinogenic toxicants, switching to a cMRTP use should also lead to a significant reduction in urinary genotoxicity (a biomarker of total genotoxic exposure) compared with continued smoking and approach the urinary genotoxicity observed upon smoking abstinence [37].…”
Section: The Approachmentioning
confidence: 99%